Eicosapentaenoic acid (EPA) exhibits antioxidant activity via mitochondrial modulation. (30th March 2022) - Xiao, Baoping; Li, Yuanyuan; Lin, Yanqi; Lin, Jingyu; Zhang, Lingyu; Wu, Daren; Zeng, Jun; Li, Jian; Liu, Jing wen; Li, Guiling
Highlights: EPA reduced both the cellular and mitochondrial ROS levels of HepG2 cells. EPA promoted cell antioxidant capacity via enhancing the antioxidant enzymes. EPA regulated mitochondrial function and increased mitochondrial biogenesis. Abstract: Reactive oxygen species (ROS) are mitochondrial respiration byproducts, the accumulation of which may cause oxidative damage and is associated with several chronic health problems. As an essential unsaturated fatty acid, eicosapentaenoic acid (EPA) provides various physiological functions; however, its exact regulatory role remains elusive. The current study aimed to address how EPA regulates cellular antioxidant capacity and the possible mechanisms of action. Upon 48 h of EPA treatment, the ROS levels of HepG2 cells were reduced by at least 40%; the total cellular antioxidant capacity was increased by approximately 50–70%, accompanied by enhanced activities and expression of major antioxidant enzymes. Furthermore, the mitochondrial membrane potential and the mitochondrial biogenesis were dramatically improved in EPA-treated cells. These data suggest that EPA improves cellular antioxidant capacity by enhancing mitochondrial function and biogenesis, which sheds light on EPA as a dietary complement to relieve the oxidative damage caused by chronic diseases.